ЖИСМОНИЙ ТАРБИЯ ВА СПОРТНИ ЯНАДА ОММАЛАШТИРИШ АСОСИДА СОҒЛОМ ТУРМУШ ТАРЗИНИ ҚАРОР ТОПТИРИШ МАСАЛАЛАРИ - Калжанов, П.У.; Ережепов, А.Ж.; Калжанов, Р.П. (SCIENCE and SOCIETY, 2019)
The article deals with the the issues of promoting a healthy lifestyle based on the further spread of physical education and sport. The sustainability of sports is scientifically grounded by the author through the introduction of sport into the minds of young people on the basis of sustainable development of sport today.
Keywords: mass sports; public health; sport events; sport competitions; sport infrastructure; international sport competitions